Online Home Pharmacy Care Prototype - Putri Diana Savita; Dwiky Miftahuda; Winda Alawiyah Safi'a; Prasojo Pribadi; Setiyo Budi Santoso (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2022)
This article presents the design of an online pharmacy service application at home. Development of application workflows using software in the draw.io network. The development includes a consultation menu, ordering medication/prescription redemption, camera features to take pictures (prescriptions), payments, and delivery messages.